ANALISIS DAMPAK UKURAN PERUSAHAAN, OPINI AUDIT, DAN REPUTASI KAP TERHADAP AUDIT DELAY PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2010–2016 - Irmalia, Yusi Nur; Khusnah, Hidayatul; Wahyuningtyas, Endah Tri (Universitas Nahdlatul Ulama Surabaya, 2018)
The purpose of this study was to analyze the firm size, audit opinion, and reputation of public accountant on audit delay. The data used in this research was secondary data, taken from the annual report 2010 to 2016 of mining companies listed at the Indonesia Stock Exchange. The samples consist of 133 firms from 2010 through 2016 and still listed. The analysis tools to test hypothesis are logistic regression analysis by using SPSS 20 with the degree of significance at 0.05. The empirical result of the study show that the firm size, audit opinion, and reputation of public accountant simultaneously have a positive influence on audit delay. The firm size has no positive effect on audit delay. While audit opinion, and reputation of public accountant have a positive influence on audit delay